2017
DOI: 10.1098/rsif.2017.0560
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of micro-scale soil deformation around roots using four-dimensional synchrotron tomography and image correlation

Abstract: This study applied time lapse (four-dimensional) synchrotron X-ray computed tomography to observe micro-scale interactions between plant roots and soil. Functionally contrasting maize root tips were repeatedly imaged during ingress into soil columns of varying water content and compaction. This yielded sequences of three-dimensional densiometric data, representing time-resolved geometric soil and root configurations at the micronmetre scale. These data were used as inputs for two full-field kinematic quantific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Thicker roots are generally better at penetrating strong soils (Chimungu et al, 2015), and indeed thickening of roots in strong soils has been interpreted as a mechanism of overcoming limiting axial stress by loosening the soil at the root tip (Hettiaratchi, 1990). Furthermore, the shape of the root tip (Colombi et al, 2017b) and the release of mucilage at the root cap have been shown to influence root penetration (Iijima et al, 2003;Vollsnes et al, 2010;Keyes et al, 2017). In naturally structured soils, roots can overcome large localised mechanical impedance by compensatory extension into loose soil compartments or macropores (Bingham & Bengough, 2003;Colombi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thicker roots are generally better at penetrating strong soils (Chimungu et al, 2015), and indeed thickening of roots in strong soils has been interpreted as a mechanism of overcoming limiting axial stress by loosening the soil at the root tip (Hettiaratchi, 1990). Furthermore, the shape of the root tip (Colombi et al, 2017b) and the release of mucilage at the root cap have been shown to influence root penetration (Iijima et al, 2003;Vollsnes et al, 2010;Keyes et al, 2017). In naturally structured soils, roots can overcome large localised mechanical impedance by compensatory extension into loose soil compartments or macropores (Bingham & Bengough, 2003;Colombi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Zappala et al (2013) previously observed that plant health was not significantly affected provided plants were not exposed to X-rays for prolonged periods. This has also been confirmed by Keyes et al, (2017a) who monitored microscale plant root growth using SRXCT and were able to mitigate the negative effects of X-rays on plant health by limiting exposure. Finally, sections of leaf and stem, excised and mounted as described below, were imaged 25 h after the initial addition of contrast media ('Leaf Images').…”
Section: Synchrotron X-ray Ct Imagingmentioning
confidence: 61%
“…We would not have captured changes in root growth caused by the addition of contrast media as the contrast media was only applied to the roots for the imaging period of 24 h and the root tips themselves were not captured. The purpose of this investigation was to assess whether our system would facilitate contrast media uptake however, were growing root tips to be imaged, such as in the work of Keyes et al, (2017a), it would be possible to capture effects of contrast media on root growth over time. In order to mitigate these effects, non-ionic iodinated contrast media should be used, such as the iopamidol used in this investigation, as ionic alternatives have previously been observed to induce more significant osmotic stress effects in biological tissues (Haller and Hizoh 2004;Hasebroock and Serkova 2009;Heinrich et al 2005;Sendeski 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to analyze the soil bulk density. In the recent decade, CT had been widely used to evaluate the evolution of the internal structure of soil by several researchers including Oda et al [2], Pires et al [3], Alshibli et al [4], Schäffer et al [5,6], Hall et al [7], Willson et al [8], Bruchon et al [9], Naveed et al [10] and Keyes et al [11].…”
Section: Introductionmentioning
confidence: 99%